HUBUNGAN ANTARA POLA ASUH ORANGTUA DENGAN KEMAMPUAN SOSIALISASI PADA REMAJA KELAS X DI SMA N 1 WANADADI KABUPATEN BANJARNEGARA - Adi Ryanto; Rahmaya Nova Handayani; Murniati - (Universitas Harapan Bangsa Purwokerto, 2016)
Family is the most important part of social networking on teenagers that is in theapplication of parenting. Parenting is a method used in the continues interaction processbetween parents and children use in order to make a gin order to make a good relationshipwith care and rules as well as to keep the development and survival. A good relationshipbetween parents and teenager will help in coaching teenager on social skills withenvironment and surounding. The research aims to know the relationship betweenparenting with social skills on teenagers of class X in senior high school of state 1 Wanadadi in Banjarnegara Region. The research methodology is analytical surveymethode with cross-sectional approach. The respondents in this research were all studentsof class X in senior high school of state 1 Wanadadi that were 74 respondents, collectedwith simple random sampling technique. The statistical test was chi-square test. Theresearch results show that there is a relationship between parenting with social skills onteenager with Ï value=0.000 (p<0.05). It proves that parenting has relationship withsocial skills of teenagers in senior high school of state 1 Wanadadi. Keywords: parenting, social skills, teenager